1999
DOI: 10.1002/(sici)1521-4095(199906)11:9<745::aid-adma745>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Oblique Incidence Organic Molecular Beam Deposition and Nonlinear Optical Properties of Organic Thin Films with a Stable In-Plane Directional Order

Abstract: Organic thin films with non-centrosymmetric ordering of dipoles are very attractive as waveguides for nonlinear optic and electro-optic applications. [1,2] High electric field poling or self-assembly has been widely used to align dipolar molecules perpendicular to the film surface. [2] However, only a few examples of in-plane alignment of dipolar molecules have been described, including epitaxy on a lattice-matched organic substrate surface, [3,4] in-plane poling, [5] and Langmuir±Blodgett film deposition. [6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 2 publications
(3 reference statements)
0
23
0
Order By: Relevance
“…Specifically, we employed the two molecular building blocks 4-[trans-2-(pyrid-4-yl-vinyl)]benzoic acid (PVBA) and 4-[(pyrid-4-yl-ethynyl)]-benzoic acid (PEBA) designed for nonlinear optics applications. [25][26][27][28] The structure formulas given in Figure 1 show that the two molecules are similar. Both species are rigid and planar.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we employed the two molecular building blocks 4-[trans-2-(pyrid-4-yl-vinyl)]benzoic acid (PVBA) and 4-[(pyrid-4-yl-ethynyl)]-benzoic acid (PEBA) designed for nonlinear optics applications. [25][26][27][28] The structure formulas given in Figure 1 show that the two molecules are similar. Both species are rigid and planar.…”
Section: Introductionmentioning
confidence: 99%
“…Some molecular glasses are also characterized by some intrinsic noncentrosymmetric order when vapor deposited, [81–85] but were not developed for second‐order nonlinear optics or electro‐optics. Other examples of relevant systems are mixtures of nonlinear optical molecules and liquid‐crystal‐like molecules, which can show a second‐order nonlinear optical activity when poled by an electric field, [86] or self‐assembled films with an orientational order governed by directional hydrogen bonding [87,88] …”
Section: Nonlinear Opticsmentioning
confidence: 99%
“…This was shown to result in a non-centrosymmetric thin film with the preferential order in the direction of the molecular beam. [25][26][27] Figure 1 shows the configuration of the deposition apparatus. As a base material, one sublimes amorphous supramolecular polymers of small molecules that are linked in a head-to-tail fashion by strong hydrogen bonding.…”
Section: Deposition Techniquesmentioning
confidence: 99%
“…[25] Figure 6 shows scanning tunneling microscopy (STM) images of submonolayer PVBA grown on Ag (111), [44,45] where it is observed that the molecules self-assembled into ordered, hydrogen-bonded chains.…”
Section: Oblique-incidence Mbdmentioning
confidence: 99%